Molecular structure, vibrational spectroscopic, natural bond orbital analysis, frontier molecular orbital analysis and thermodynamic properties of N-tert-butoxy carbonyl-L-phenylalanine by DFT methods. (19th September 2019) - Raja, B.; Balachandran, V.; Revathi, B.; Anitha, K.
Abstract: The FT-IR and FT-Raman spectra of N-tert-butoxy carbonyl-L-phenylalanine (NTBCLPA) molecule have been recorded in the region 4000–400 cm −1 and 3500–100 cm −1 respectively. Optimized geometrical structure, harmonic vibrational frequencies, and intensities have been computed by the B3LYP density functional levels using ccPVDZ and 6-31+G(d) basis sets. The observed FT-IR and FT-Raman vibrational frequencies are analyzed. The geometries and normal modes of vibration obtained from DFT method are in good agreement with the experimental data. The charge transfer occurring in the molecule between HOMO and LUMO energies, frontier energy gap, the molecular electrostatic potential (MEP) were calculated and analyzed. The statistical thermodynamic functions (heat capacity, entropy, vibrational partition function and Gibbs energy) were obtained for the range of temperature 100–1000 K.